Pengembangan Perilaku Asertif untuk Pencegahan Penyalahgunaan Narkoba Melalui Layanan Bimbingan Kelompok - Sofah, Rahmi; Harlina, Harlina; Putri, Rani Mega (STKIP Muhammadiyah Pringsewu, 2018)
Acts of drug abuse now in a critical, even already spread among students. One of the attitudes that should be developed by students to avoid drug abuse is assertiveness. To develop assertiveness, Counseling teachers/ counselors can train them in group guidance services. This paper uses experiment methods with one group pretest and posttest design. Samples are students who have low scores on assertive behavior. Instrument assertiveness use a questionnaire with Likert scale. This research uses t test statistic analysis. Too many nouns The result of research shows that there is the influence of group counseling service toward assertive behavior for prevention of drug abuse got t test (7, 043) >t table(1, 83) with Î±=0,05.Keywords: Group Guidance, Assertive, Drug abuse